Outcomes of cochlear implantation in 75 patients with auditory neuropathy - Jie Wu; Jiyue Chen; Zhiwei Ding; Jialin Fan; Qiuquan Wang; Pu Dai; Dongyi Han (Frontiers in Neuroscience, 2023)
BackgroundCochlear implantation (CI) outcomes in patients with auditory neuropathy (AN) are variable, which hampers patients’ decisions on CI.ObjectiveThis study aims to assess the outcomes of CI in individuals diagnosed with AN and to examine the various factors that may influence the effectiveness of this intervention.MethodsA total of 75 patients diagnosed with AN were included in the study. The hearing threshold, the score of categories of auditory performance (CAP), speech intelligibility rating (SIR), and speech audiometry were tested. Genetic testing was conducted by medical exome sequencing in 46 patients.ResultsAfter CI, the average aided hearing threshold for patients with prelingual and post-lingual onset was 38.25 ± 6.63 dB and 32.58 ± 9.26 dB, respectively; CAP score improved to 5.52 ± 1.64 (p < 0.001) and 6.00 ± 0.96 (p < 0.001), respectively; SIR score increased to 3.57 ± 1.22 (p < 0.001) and 4.15 ± 0.95 (p < 0.001), respectively. Maximum speech recognition ranged from 58 to 93% for prelingual onset patients and 43 to 98% for those with post-lingual onset. Speech outcomes of CI in cases with cochlear nerve (CN) deficiency were significantly poorer (p = 0.008). Molecular etiologies, including TWIST1, ACTG1, m.A7445G, and a copy-number variant (CNV) carrying ACTB, were related to AN here.ConclusionCI is a viable therapy option for patients with AN; CN deficiency might impact outcomes of CI.